Дослідження та порівняльний аналіз зносостійкості литих мелючих тіл з хромистих чавунів - Ломакін, В. М.; Кропівний, В. М.; Пукалов, В. В.; Кропівна, А. В.; Молокост, Л. А.; Lomakin, V.; Kropivnyi, V.; Pukalov, V.; Kropivna, O.; Molokost, L. (ЦНТУ, 2022)
Випробувано мелючі тіла, відлиті з хромистого чавуну в багатомісному кокілі, на ударно- абразивну зносостійкість і ударостійкість. Для дослідження прийнято три типи хромистих чавунів: низькохромистий (~1% Cr), середньохромистий (до 5% Cr) і високохромистий (ВХБЧ, до 20% Cr). Досліджено макро- і мікроструктуру зазначених сплавів, як матеріалу литих мелючих куль. Встановлено підвищення ударно-абразивної зносостійкості і ударостійкості таких виробів при збільшенні масової частки хрому в чавуні за рахунок утворення в металевій основі карбідів типу (Fe, Cr)3C і особливо (Fe, Cr)7C3. Економічно обґрунтовано в якості матеріалу мелючих куль низькохромистий білий чавун. A study was made of the impact-abrasive wear resistance and impact resistance of grinding bodies cast in a multi-place mold. Three types of chromium cast irons were adopted for the study: low chromium (~1% Cr), medium chromium (up to 5% Cr) and high chromium (up to 20% Cr). The macro- and microstructure of these alloys as a material for cast grinding balls has been studied. Installed an increase in the impact-abrasive wear resistance and impact resistance of such products with an increase in the mass fraction of chromium in cast iron due to the formation of carbides of the (Fe, Cr)3C and especially (Fe, Cr)7C3. Balls were cast in multi-seat chill molds. Cast iron was smelted in a medium-frequency induction furnace, such as IChT, with the main lining on a charge of pure pig iron and steel low-carbon scrap. The temperature of cast iron production was 1500 °C. Liquid cast iron was subjected to alloying with medium carbon ferrochrome. The wear resistance of cast irons was determined on samples cut from balls in the radial direction. The tests were performed in a laboratory mill When tested for impact resistance, the grinding ball received a striking blow of mass 50 kg, falling from a height of 0,5 m. The frequency of application of dynamic loads was 10 beats per minute. Impact resistance was determined by the average number of impacts sustained by the grinding body prior to destruction. Nevertheless, significant excess of the cost high-chromium over low-chromium cast iron forces us to agree with the opinion of the majority of researchers and the practice of production of such metal products. In today's conditions, low-chromium white cast iron is an economically viable material for grinding media.
Research and Comparative Analysis of Wear Resistance of Cast Grinding Media From Chromium Cast Irons
Keywords: чавун; розплав; кокіль; куля; легування; хром; зносостійкість; ударостійкість; cast iron; melt; chill mold; ball; alloying; chromium; wear resistance; shock resistance